2013
DOI: 10.1073/pnas.1302445110
|View full text |Cite
|
Sign up to set email alerts
|

Decreased water flowing from a forest amended with calcium silicate

Abstract: Acid deposition during the 20th century caused widespread depletion of available soil calcium (Ca) throughout much of the industrialized world. To better understand how forest ecosystems respond to changes in a component of acidification stress, an 11.8-ha watershed was amended with wollastonite, a calcium silicate mineral, to restore available soil Ca to preindustrial levels through natural weathering. An unexpected outcome of the Ca amendment was a change in watershed hydrology; annual evapotranspiration inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…Predicting the impact of trees on stream chemistry therefore depends on understanding the degree of connection between the hillslope and the stream (Herndon et al, 2015). According to this hypothesis, biogeochemical processes such as cation exchange occurring in matrix waters can influence ecological responses in streams under conditions of high connectivity (e.g., Green et al, 2013).…”
Section: Hypothesis 8 Mycorrhizal Fungi Can Use Matrixmentioning
confidence: 99%
“…Predicting the impact of trees on stream chemistry therefore depends on understanding the degree of connection between the hillslope and the stream (Herndon et al, 2015). According to this hypothesis, biogeochemical processes such as cation exchange occurring in matrix waters can influence ecological responses in streams under conditions of high connectivity (e.g., Green et al, 2013).…”
Section: Hypothesis 8 Mycorrhizal Fungi Can Use Matrixmentioning
confidence: 99%
“…Only five of the 62 stations show negative trends in streamflow, with the rest showing increases of up to 45%. The change in streamflow for the relatively undisturbed reference watershed at the HBEF (Watershed 3) is at the 95th percentile, and is exceeded slightly by a watershed that was amended with Ca (W1; Green et al 2013). Forest harvesting experiments caused high flows early in the record, which affected the streamflow trends at these sites, resulting in less dramatic increases (13% and 29% change).…”
Section: Changes In Climate and Hydrologymentioning
confidence: 99%
“…Nezat et al (2010) found that it took 3-9 years for the applied Ca to infiltrate the deeper flow paths in the soil profile before it was exported to the stream. Within this same watershed, Green et al (2013) found that stream flow was increased due to reduced rates of evapotranspiration for three years, before returning to pre-treatment levels. They attributed this to increased aboveground productivity due to the short term correction of a nutrient imbalance, as found in other studies (e.g., Kulmatiski et al, 2007).…”
mentioning
confidence: 97%
“…) was applied to a forested catchment with Ca depleted soils and the responses have been extensively studied (Juice et al, 2006;Nezat et al, 2010;Green et al, 2013). Juice et al (2006) found that Ca addition increased the pH of the Oi + Oe horizons from 3.8 to 5.0 and the Oa horizon from 3.9 to 4.2 within 3 years of treatment; foliar and fine root Ca concentrations also increased.…”
mentioning
confidence: 99%